we can always get the common ratio of a geometric sequence by simply dividing the current term by the previous term, in this case for the sake of simplicity let's divide 2/3 by 2, so
![\cfrac{2}{3}/ 2\implies \cfrac{2}{3}/ \cfrac{2}{1}\implies \cfrac{2}{3}\cdot \cfrac{1}{2}\implies \cfrac{1}{3}\impliedby \textit{common ratio}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7dqrqft3i3mnu2t7dh3igel5l8dztnfv3u.png)
so the sequence more or less looks like
![2~~,~~\cfrac{2}{3}~~,~~\cfrac{2}{9}~~,~~\cfrac{2}{81}~~,~~\cfrac{2}{243}](https://img.qammunity.org/2023/formulas/mathematics/high-school/o3f7jgjmdkme8huzb9ze2wtqcn9h53nauw.png)
so we'd want the sum of the first 5 terms
![\qquad \qquad \textit{sum of a finite geometric sequence} \\\\ \displaystyle S_n=\sum\limits_(i=1)^(n)\ a_1\cdot r^(i-1)\implies S_n=a_1\left( \cfrac{1-r^n}{1-r} \right)\quad \begin{cases} n=\textit{last term's}\\ \qquad position\\ a_1=\textit{first term}\\ r=\textit{common ratio} \end{cases} \\\\\\ S_5=2\left( \cfrac{1~~ - ~~((1)/(3))^5}{1~~ - ~~(1)/(3)} \right)\implies S_5=2\left( \cfrac{~~(242)/(243)~~}{(2)/(3)} \right)\implies S_5=\cfrac{242}{81}\implies S_5=2(80)/(81)](https://img.qammunity.org/2023/formulas/mathematics/high-school/m984zf7bzr8q06dmbhi747uawvhio82d2x.png)